Research Status and Development of Precision Analysis of CNC Machine Tools. Issue 2 (April 2021) - Dou, Yifan; Zhang, Genbao; Ran, Yan
Abstract: Accuracy is a key quality characteristic of CNC machine tools, reflecting the pros and cons of machine tool performance. Accuracy is affected by performance failures of CNC machine tools, such as vibration, friction, and heat transfer. Therefore, it is difficult to accurately model and comprehensively analyse the accuracy of the machine tool by studying the influence of certain factors on the accuracy of the CNC machine tool in isolation, which makes it difficult to find out the problems in the design or manufacturing process. The article analyses the current status and research significance of domestic CNC machine tool accuracy, expounds the domestic and foreign research status of CNC machine tool accuracy modelling method and CNC machine tool accuracy comprehensive analysis, summarizes the existing problems and development trends of CNC machine tool accuracy research, and compares it based on the meta-action. The theoretical systematic modelling of the accuracy of CNC machine tools and the key issues of comprehensive evaluation of the accuracy of CNC machine tools combined with the meta-action chain provide insights and provide analytical methods for the design and manufacture of CNC machine tools.